Human Pancreatic Carcinoma-Associated Fibroblasts Promote Expression of Co-inhibitory Markers on CD4+ and CD8+ T-Cells - Gorchs, Laia; Fernández Moro, Carlos; Bankhead, Peter; Kern, Katharina P.; Sadeak, Imrul; Meng, Qingda; Rangelova, Elena; Kaipe, Helen (Frontiers in Immunology, 2019)
Carcinoma-associated pancreatic fibroblasts (CAFs) are the major type of cells in the stroma of pancreatic ductal adenocarcinomas and besides their pathological release of extracellular matrix proteins, they are also perceived as key contributors to immune evasion. Despite the known relevance of tumor infiltrating lymphocytes in cancers, the interactions between T-cells and CAFs remain largely unexplored. Here, we found that CAFs isolated from tumors of pancreatic cancer patients undergoing surgical resection (n = 15) expressed higher levels of the PD-1 ligands PD-L1 and PD-L2 compared to primary skin fibroblasts from healthy donors. CAFs strongly inhibited T-cell proliferation in a contact-independent fashion. Blocking the activity of prostaglandin E2 (PGE2) by indomethacin partially restored the proliferative capacity of both CD4+ and CD8+ T-cells. After stimulation, the proportion of proliferating T-cells expressing HLA-DR and the proportion of memory T-cells were decreased when CAFs were present compared to T-cells proliferating in the absence of CAFs. Interestingly, CAFs promoted the expression of TIM-3, PD-1, CTLA-4 and LAG-3 in proliferating T-cells. Immunohistochemistry stainings further showed that T-cells residing within the desmoplastic stromal compartment express PD-1, indicating a role for CAFs on co-inhibitory marker expression also in vivo. We further found that PGE2 promoted the expression of PD 1 and TIM 3 on T-cells. Functional assays showed that proliferating T-cells expressing immune checkpoints produced less IFN-, TNF-, and CD107a after restimulation when CAFs had been present. Thus, this indicates that CAFs induce expression of immune checkpoints on CD4+ and CD8+ T-cells, which contribute to a diminished immune function.